Abastecimiento de Repuestos y Accesorios que afecta a la maquinaria y a los Ingresos en la Empresa “I.L.G.A. IMPORTADORA” Cía. Ltda. Sucursal Vinces – Los Ríos - Triana Sosa, Tatiana Katherine (2018)
The company "I.L.G.A. IMPORTADORA "CÍA LTDA Branch Vinces - Los Ríos, is a private sector company where this case study was developed, with the theme of SUPPLY OF SPARE PARTS AND ACCESSORIES THAT AFFECTS THE MACHINERY AND THE INCOME OF THE COMPANY "I.L.G.A IMPORTADORA" CÍA LTDA Branch Vinces - Los Ríos. Located in the research sub-line GESTION DE ACCOUNTING INFORMATION. In this way find a more genuine way for the provision of resources and supplies of inventory for spare parts and accessories that the machinery is lacking. The objective of this case study is to improve the supply process to generate higher earnings. For the execution of this topic he focused especially on the income of the entity, where expenses are appreciated, but revenues are not projected and results are not generated for the damages caused by the machinery in operation and the schedule of activities of the entity are not made. Because the company "I.L.G.A. IMPORTADORA "CÍA LTDA It is a globally recognized brand, so that to the mishaps of the machinery certain quantity of spare parts, accessories (computer PCM and Computer ECM, Arnet, etc.), no found in the Vinces Branch or in the same city, so you have to wait a while prudential for the repair of machinery. Although if the solution of the repair of the machinery is not immediate because the technician or operator of the company, requires a spare that there is no company inventory "I.L.G.A IMPORTADORA" CÍA LTDA Branch Vinces - Los Ríos, this will be forced to request the matrix of the same, but there is the spare that is requires in the company I.L.G.A IMPORTADORA "CÍA LTDA or in the country, it must be acquired abroad.